Modification of high-entropy alloy AlCoCrFeNi by electron beam treatment - Victor Gromov; Yurii Ivanov; Sergey Konovalov; Kirill Osintsev; Alexander Semin; Yulia Rubannikova (Journal of Materials Research and Technology, 2021)
In this study, a high-entropy alloy (HEA) of Al–Co–Cr–Fe–Ni system was fabricated via wire-arc additive manufacturing technology (WAAM) in the atmosphere of pure Ar followed by high-intensity electron beam treatment. SEM, TEM, and X-ray diffraction methods were used to characterize the manufactured material's microstructure. The HEA has the following composition: Al (36.5 at. %), Ni (33.7 at. %), Fe (16.4 at. %), Cr (8,6 at. %) and Co (4.9 at. %). The obtained material without electron beam treatment has a polycrystalline structure with a grain size of 4–15 μm. Bulks of grains are enriched in Al and Ni, while grain boundaries contain Cr and Fe. Co is quasi-uniformly distributed in the crystal lattice of the manufactured HEA. The ultimate material strength in testing for compression depends on production mode and varies within the interval from 652 to 1899 MPa. The HEA wear parameter amounts to 1.4∙10−4 mm3/N∙m, friction coefficient - 0.65. In testings for tension, the material failure occurred by the mechanism of intragrain cleavage. The formation of brittle cracks along boundaries and in grain boundary junctions, i.e. in sites containing the inclusions of second phases, is revealed. The HEA's irradiation by a pulsed electron beam with the energy density of 10–30 J/cm2 (pulse duration 200 μs, number of pulses 3) results in material homogenization, decreased crystal lattice microdistortions, and an increase in sizes of coherent scattering regions. High-velocity crystallization of the molten surface layer of HEA samples is accompanied by columnar structure formation having a submicro-nanocrystalline structure.